Conceito de análise em frasco único: determinação de ferro em biodiesel por microextração líquido-líquido dispersiva em fase reversa e detecção por imagem digital - Bif, Eduarda (2023)
Environmentally designed, miniaturized analytical procedures that minimize systematic and random errors are of great interest in the field of analytical chemistry. Single vial analysis meets these conditions due to the possibility of preparing and detecting the analyte of interest in a single vial and its effect is enhanced when associated with a miniaturized sample preparation method. The presence of transition metals such as iron in biodiesel, even in low concentrations, can accelerate the oxidation process of the biofuel and cause a reduction in its useful life. Therefore, developing alternative methods to identify the presence and quantify this metal in the sample is essential to mitigate risks, since Brazilian and foreign standards do not regulate the presence of Fe in B100 biodiesel and, consequently, indicate the analytical tests to determine it. In this research, a method was developed using reversed-phase dispersive liquid-liquid microextraction (RP-DLLME) for the extraction and pre-concentration of Fe in biodiesel samples. The determination of this metal in the sample was carried out by digital image acquisition with calibration carried out by fortification in the matrix. The following parameters were investigated when optimizing the sample preparation method: dispersing solvent, dispersing/extracting solvent solution ratio, type of acid used as the extracting solvent, pH of the extracting solution, SCN- ion concentration, solvent solution volume, use of ultrasound radiation, temperature and centrifugation time. For the method optimization stage, the samples were prepared with the addition of an organometallic standard for Fe 100 µg g-1 (Specsol, Brazil). In order to choose the best result for the parameters for iron determination by digital imaging, the tests were carried out in triplicate and interpreted according to the result of the vector standard, proposed by Lyra et al (2008). The quantification limit of the proposed method was obtained from the value of the first point on the calibration curve and the detection limit was calculated from the LQ. The results obtained for the LQ and LD were 0.5 mg L-1 and 0.15 mg L-1, respectively. The addition and recovery tests of the proposed method were carried out by adding the standard in two different concentrations (0.5 µg g-1 and 3.0 µg g-1) to two samples with additives and two without. The results obtained were satisfactory for the samples without additives (90 - 96%), while the recovery results for the samples with additives were slightly lower (69 - 78%). The results obtained using the proposed method (RP-DLLME/Digital Imaging) were compared with the results obtained by emulsion break induced extraction (EIQE) and determined by flame atomic absorption spectrometry, on five biodiesel samples, three with additives and two without. It was found that there was no statistical difference between the two methods (5% significance level). RP-DLLME stood out for using diluted acids in lower volumes, for its simplicity and low cost, for making it possible to carry out the sample preparation, reaction and determination stages in a single vial, and for reducing the number of steps and time spent on the process.